2019
DOI: 10.3892/etm.2019.7734
|View full text |Cite
|
Sign up to set email alerts
|

Immune promotive effect of bioactive peptides may be mediated by regulating the expression of SOCS1/miR‑155

Abstract: The present study was designed to evaluate the effect of bioactive hepatic peptide (BHP) on the immune function of mice and to examine the mechanism mediated by the related factors cytokine suppressor of cytokine signaling 1 (SOCS1) and microRNA (miR)-155. The mice were divided into eight groups, including a normal mouse group, normal peptide groups (low-dose, mid-dose and high-dose), an immunosuppressed group, and immunosuppressed with peptide groups (low-dose, mid-dose and high-dose). The proliferative abili… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
18
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(20 citation statements)
references
References 46 publications
(46 reference statements)
1
18
0
Order By: Relevance
“…Marine species contain physiologically bioactive components for active pharmaceutical ingredients and are an important compound for human nutrition. Marine peptides, particularly, have attracted a lot of interest because of their potential for improving health and lowering illness risk [ 22 , 23 , 24 ]. Peptides may play a significant role in the intestine by regulating digestive enzymes, stabilizing the intestinal epithelial tight junctions, and modulating dietary absorption [ 25 , 26 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Marine species contain physiologically bioactive components for active pharmaceutical ingredients and are an important compound for human nutrition. Marine peptides, particularly, have attracted a lot of interest because of their potential for improving health and lowering illness risk [ 22 , 23 , 24 ]. Peptides may play a significant role in the intestine by regulating digestive enzymes, stabilizing the intestinal epithelial tight junctions, and modulating dietary absorption [ 25 , 26 ].…”
Section: Introductionmentioning
confidence: 99%
“…Peptides may play a significant role in the intestine by regulating digestive enzymes, stabilizing the intestinal epithelial tight junctions, and modulating dietary absorption [ 25 , 26 ]. Peptide hydrolysate from marine sources is safe, physiologically beneficial, improves immunity, and performs a variety of functions, i.e., anticancer, antibacterial, antiviral, antihypertensive, antithrombotic, hormonal, and cholesterol-lowering effects [ 20 , 22 , 23 , 27 ]. It has been reported that shark-derived hydrolysate upregulates the cytokines production and protects intestinal epithelial [ 24 ].…”
Section: Introductionmentioning
confidence: 99%
“…The spleen is the principal peripheral lymphoid organ in the body and is the location of B and T cells. Lymphocyte activity and proliferation in the spleen represent its immune ability and the cellular immune function of the body [ 46 ]. Here we showed increased proliferation of splenocytes in response to treatment with naringenin and its combination with CPT, suggesting that these two compounds influence the immune system.…”
Section: Discussionmentioning
confidence: 99%
“…Unless otherwise stated, all chemicals, media and supplements used in this study were purchased from Sigma Aldrich (Shanghai, China). The BAPT with the special characteristic of ubiquitin enzyme and molecular weight as 8Kd were derived from spleen of small-tailed-Han sheep and identified by Professor Su’s research group at Inner Mongolia Medical University (Hohhot, China) with the RRLC-MS method [ 22 , 50 52 ].…”
Section: Methodsmentioning
confidence: 99%
“…8 The fertilization rates and embryonic developmental rates in different groups. Note: Labeling with the different letter in each column indicates significant differences between different groups (P < 0.05) as 8Kd were derived from spleen of small-tailed-Han sheep and identified by Professor Su's research group at Inner Mongolia Medical University (Hohhot, China) with the RRLC-MS method [22,[50][51][52].…”
Section: Chemicalsmentioning
confidence: 99%